2016
DOI: 10.1007/s13520-016-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on environmental sustainability practices of star hotels in Bangalore

Abstract: The hotel industry has been showing their responsibility towards sustainability by employing green practices in their daily operations. The area of sustainability in hospitality relates to incorporating sustainability in operations and focusing on practices like saving energy, using renewable energy, and recycling waste. The hotels are showing their commitment to sustainability indicators like social, economic, and environmental concerns and communicating about the same to their customers. With the help of sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A recent study by the world's leading hotel room booking company (Booking.com) found that 87 per cent of 4,768 respondents surveyed wanted to travel sustainably and 68 per cent of those wanted to stay in ecofriendly hotels (Sustainable Travel Report, 2018). In an attempt to attract customers and maintain growth and profitability, hotels are responding to green-conscious stakeholders by using ESPPs (Edwards, 2005;Leonidou et al, 2013;Shanti, 2016). However, many hotels do not have a coherent environmental strategy and sometimes implement environmentally IJCHM 31,6 sustainable practices in an ad hoc manner (Dewhurst and Thomas, 2003;Shanti, 2016).…”
Section: Sustainable Policies and Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by the world's leading hotel room booking company (Booking.com) found that 87 per cent of 4,768 respondents surveyed wanted to travel sustainably and 68 per cent of those wanted to stay in ecofriendly hotels (Sustainable Travel Report, 2018). In an attempt to attract customers and maintain growth and profitability, hotels are responding to green-conscious stakeholders by using ESPPs (Edwards, 2005;Leonidou et al, 2013;Shanti, 2016). However, many hotels do not have a coherent environmental strategy and sometimes implement environmentally IJCHM 31,6 sustainable practices in an ad hoc manner (Dewhurst and Thomas, 2003;Shanti, 2016).…”
Section: Sustainable Policies and Practicesmentioning
confidence: 99%
“…In an attempt to attract customers and maintain growth and profitability, hotels are responding to green-conscious stakeholders by using ESPPs (Edwards, 2005;Leonidou et al, 2013;Shanti, 2016). However, many hotels do not have a coherent environmental strategy and sometimes implement environmentally IJCHM 31,6 sustainable practices in an ad hoc manner (Dewhurst and Thomas, 2003;Shanti, 2016). Despite the progress made by hotels in becoming more sustainable, they are still struggling to promote this effectively to their stakeholders (Peir o-Signes et al, 2014).…”
Section: Sustainable Policies and Practicesmentioning
confidence: 99%
“…In an attempt to attract customers and to maintain growth and profitability, hotels are increasingly responding to the values of environmentally conscious stakeholders (Shanti, 2016). Previous studies have identified a combination of factors that compel hoteliers to consider these environmental practices more carefully.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hotel sustainability has its roots in the 1960s, stating that greater attention has been given to environmental and social impacts, which result from hotel activities and development [24]. Over the course of the last 50 years, many definitions have been advanced that capture the meaning of 'sustainable hotels'.…”
Section: Sustainable Hotelsmentioning
confidence: 99%